2020
DOI: 10.14814/phy2.14549
|View full text |Cite
|
Sign up to set email alerts
|

Does depth of squat‐stand maneuver affect estimates of dynamic cerebral autoregulation?

Abstract: Repeated squat‐stand maneuvers (SSM) are an effective way of measuring dynamic cerebral autoregulation (dCA), but the depth of SSM required to improve dCA estimations has never been studied. We compared beat‐to‐beat cerebral hemodynamic parameters between maximal depth SSM (SSMD) and a shallower alternative (SSMS) in two age groups (younger [20–34 years] vs. older [50–71 years]) at a frequency of 0.05 Hz. Cerebral blood flow velocity, continuous blood pressure (BP) and end‐tidal CO2 (EtCO2) were measured using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…Notably, during hypercapnia, CBFV climbed consecutively with each maneuver. This could be an exercise effect directly impairing dCA (Barnes, Ball, Haunton, Panerai, et al, 2017 ; Batterham et al, 2020 ), yet no such trend is noted in the poikilocapnic state in our single participant.…”
Section: Discussionmentioning
confidence: 60%
“…Notably, during hypercapnia, CBFV climbed consecutively with each maneuver. This could be an exercise effect directly impairing dCA (Barnes, Ball, Haunton, Panerai, et al, 2017 ; Batterham et al, 2020 ), yet no such trend is noted in the poikilocapnic state in our single participant.…”
Section: Discussionmentioning
confidence: 60%
“…TFA is widely used across studies of autoregulation to allow the estimation of dCA parameters from spontaneous rather than induced BP fluctuations [ 127 ]. For research studies focusing on older participants, this is particularly advantageous as this can be better tolerated than the thigh-cuff and squat-stand manoeuvre [ 4 ]. In a longitudinal study of ten subjects who were followed for 10 years, ARI measured by TFA was found to decrease, suggesting dCA became less efficient with age [ 13 ].…”
Section: Cerebral Autoregulationmentioning
confidence: 99%
“…Thus, many studies of older adults instead use the sit-to-stand manoeuvre, which also generates a transient response of CBF to changes in BP, if measurements are taken immediately after standing up [ 64 , 128 ]. Recently, an older group of individuals (aged 50–71 years) as compared to a younger group (20–34 years) demonstrated lower ARI during maximal depth squats as compared to shallower squats—thereby suggesting less efficient dCA in older individuals during maximal depth squats as compared to rest or the shallower approach [ 4 ]. Similarly, reductions in NIRS-measured frontal cortex oxygenation were seen in 27 healthy older adults during sit-to-stand [ 65 , 66 ], and high-frequency dCA was impaired in older adults during sit-to-stand [ 74 ].…”
Section: Cerebral Autoregulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of larger oscillations in MAP to improve the reliability of CA metrics, 28,50 and facilitate the identification of the effects of ageing, is also illustrated by the findings of Batterham et al, who recently reported reduced ARI values in older subjects performing the squat-stand manoeuvre. 44 In both their younger and older groups, the sex ratio was 50%, but the influence of sex on the effect of age was not examined. Similarly, Smirl et al 42 compared groups of older and younger subjects undergoing mild exercise combined with oscillatory lower body negative pressure, which induced relatively large changes in MAP at fixed frequencies of 0.05 and 0.10 Hz.…”
Section: Influence Of Age On Dynamic Camentioning
confidence: 99%